PAI Go Digital: Teacher Innovation in Enhancing Learning Motivation and Engagement among Junior Secondary Students at SMP Negeri 1 Limbur Lubuk Mengkuang - Zainap Zainap; Siti Khamim; Ulfa Adilla; Novita Nurul Hidayah; Gio Rivaldo; Redian Saputra (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
This study examines the implementation of the PAI Go Digital instructional innovation as a teacher led strategy to enhance learning motivation and student engagement in Islamic Religious Education at SMP Negeri 1 Limbur Lubuk Mengkuang. A qualitative case study design was employed across three months of fieldwork during the running semester. Participants were Islamic Religious Education teachers and grade seven through nine students selected purposively. Data were collected through participatory observation, semi structured interviews, and documentary analysis of digital learning artifacts. Analysis followed the Miles, Huberman, and Saldaña interactive model, with credibility established through source and method triangulation as well as member checking. The findings cluster around three interlocking themes. First, the PAI teachers built a coherent four strand strategy that combined multimodal content design, interactive online assessment, curated learning platforms, and scaffolding based teacher facilitation. Second, student motivation rose consistently, marked by higher enthusiasm, more active participation in classroom discussion, and a renewed curiosity toward Islamic content. Third, engagement shifted from passive listening to active participation through online quizzes, independent exploration of digital resources, and creative task completion. Two structural constraints surfaced as well, namely limited internet connectivity and uneven student digital literacy, both moderated through teacher mentoring and adaptive media choices. The study concludes that PAI Go Digital functions as an effective pedagogical innovation when teacher competence, contextually grounded content design, and school ecosystem support move together.